1995
DOI: 10.1038/ki.1995.272
|View full text |Cite
|
Sign up to set email alerts
|

A major role for CD62P/CD15s interaction in leukocyte margination during hemodialysis

Abstract: We investigated expression of several antigens on neutrophils and monocytes, involved in cell adhesion, from patients hemodialyzed with cellulosic and polyacrylonitrile membranes. Among the antigens tested only the expression of CD15s and CD11b was significantly increased on neutrophils and monocytes in patients dialyzed with cellulosic membranes. No changes occurred with polyacrylonitrile membranes. Leukocyte counts from patients dialyzed with cuprophane membranes decreased at the same time as expression of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 39 publications
4
61
0
Order By: Relevance
“…CD11c/CD18 (CR4, p150/95), another member of the leukocyte integrin family, also showed an upregulation during dialysis with unmodified cellulose membranes (13,15,16); however this phenomenon was not confirmed by Stuard et al (10). The expression of CD11a/CD18 (LFA-1, leukocyte function antigen-1) with whatever membrane did not change during dialysis, (8, 10,11,13,15).…”
Section: Patho-physiologic Mechanismsmentioning
confidence: 85%
See 1 more Smart Citation
“…CD11c/CD18 (CR4, p150/95), another member of the leukocyte integrin family, also showed an upregulation during dialysis with unmodified cellulose membranes (13,15,16); however this phenomenon was not confirmed by Stuard et al (10). The expression of CD11a/CD18 (LFA-1, leukocyte function antigen-1) with whatever membrane did not change during dialysis, (8, 10,11,13,15).…”
Section: Patho-physiologic Mechanismsmentioning
confidence: 85%
“…No (10,13,14) or only minor (11) upregulation was observed during dialysis with polyacrylonitrile and polyamide membranes. A correlation between the upregulation of CD11b across the dialyzer at the fifth minute of dialysis and the decrease in granulocyte count was found (12).…”
Section: Patho-physiologic Mechanismsmentioning
confidence: 99%
“…The property which causes monocytes to preferentially bind platelets, a possible basis for the involvement of activated platelets in atherosclerosis (67), is at presently unknown. It has been conjectured that a different conformation ofadhesive molecules orithe monocyte surface allow a better interaction with activated platelets, and/or some additional binding mechanism may be involved (38,45). The latter might be represented by CD40-CD40 ligand interactions.…”
Section: Hemodialysis Settingmentioning
confidence: 99%
“…One study (38) reported that in patients chronically dialyzed with cuprophan membrane, almost all monocytes (80 to 95%) express pre-dialysis levels of CD62P (a marker of platelet-monocyte aggregation). Levels ofplatelet-monocyte conjugates can further increase during the hemodialysis procedure when using dialyzer membrane materials like cuprophan (38,40), cellulose diacetate (41,43), polysulphone (37) and polymethylmethacrylate (41).…”
Section: Hemodialysis Settingmentioning
confidence: 99%
See 1 more Smart Citation